Reconstruction of the complex angle-dependent photoionization transition dipole from a laser-dressed streaking experiment - Zhao, Xi; Wei, Hui; Yu, Wei-Wei; Lin, C. D. (My University, 2018)
We study the retrieval of the angular dependence of the photoionization transition dipole phase of an attosecond XUV pulse in order to reconstruct the whole photoelectron wave packet after the photoemission process. Using a one-electron model Ar atom, we show that the full electron wave packet can be reconstructed from IR-free photoelectron angular distributions and the streaking electron spectra in an IR-dressed XUV photoionization, with photoelectrons along the common polarization direction of the two pulses. The method relies on the validity of the strong-field approximation so it is valid only for higher energy photoelectrons. We also point out that a single photoionization group time delay is not enough to represent a photoemission process; instead, a complete characterization of the electron wave packet requires the retrieval of the spectral phase over the whole bandwidth of the wave packet.